Talent Management Practices and Financial Performance in Nepalese Joint-venture Commercial Banks: Employee Perspective (The Mega Journal, 2024)
This study aimed to investigate the impact of talent management practices, including talent attraction, talent development, talent retention, talent selection, and reward management, on financial performance in Nepalese banks. A questionnaire with a 5-point Likert scale was used to collect data from 256 employees from 17 Nepalese banks over a 10-year period. Structural equation modeling (SEM) was conducted using the AMOS software to analyze the data. The results showed that talent attraction, talent development, and talent retention had a significant positive impact on return on equity (ROE), while the impact of talent selection and reward management on ROE was found to be insignificant. Additionally, talent development had a significant positive impact on return on assets (ROA), while the impact of the other talent management practices on ROA was insignificant. These findings suggest that talent management practices can play a critical role in improving the financial performance of Nepalese banks, particularly in terms of ROE. The study provides valuable insights for bank managers and policymakers on the importance of talent management practices for enhancing financial performance.